Periglacial geomorphology of summit tors on Bodmin Moor, Cornwall, SW England - Evans, David J. A.; Kalyan, Ria; Orton, Chris (Taylor & Francis, 2017)
Three maps are presented that portray the periglacial geomorphology of the three summit areas of Bodmin Moor, Cornwall, SW England, including Brown Willy (scale 1:2630), Kilmar/Bearah/Sharp tors (scale 1:3335) and Rough/Little Rough/Showery tors (scale 1:2175). Landform elements include castellated tors with well-developed cantilevered or precariously balanced corestones, summit blockfields, rock-fronted lobes thought to record former permafrost creep, patterned ground (stripes) and lower slope accumulations of crudely stratified growan or weathered granite residue. The altitudinal arrangement of these periglacial landforms appears to be a signature of a well-established periglacial landsystem and hence the Bodmin Moor granite massif is a suitable exemplar for a mature upland periglacial landsystem unaffected by glacierization.